Incidence of adult primary immune thrombocytopenia in England—An update. (26th June 2022) - Doobaree, Indraraj Umesh; Conway, Katherine; Miah, Haroon; Miah, Atiqa; Makris, Michael; Hill, Quentin; Cooper, Nicola; Bradbury, Charlotte; Newland, Adrian; Provan, Drew; McDonald, Vickie
Abstract: Background: Adult primary immune thrombocytopenia (ITP) is a rare bleeding disorder of unknown cause. Recent estimates of its incidence and trend over time were acquired for England. Method: The primary ITP population (using ICD 10 code D693 and excluding secondary ITP cases; positive predictive value: 82.6%) was sourced from NHS Digital inpatient and outpatient. Incidence rate (IR) for England and by age groups, sex, and regions were calculated and trends were assessed using average annual percent change (AAPC). Results: A total of 25 805 patients (mean age 59 years; females 57.8%) diagnosed between 2003 and 2014 was identified. IRs increased from 4.2/100 000 to 6.4/100 000 over this period (AAPC:4.3%). For all sex‐specific age groups, the IRs significantly increased over time, except 18–29 years males. The greatest increase was among females aged 30–39 (AAPC:8.7%). In contrast, among ≥70 years, ITP was more common in males (highest IR among ≥80 years males: 23.9/100 000). England's average annual IR was 6.1/100 000 for 2010–14. An estimated 2.5/100 000 (based on UKITP Registry data) was estimated to require 1st line treatment whereas 2.4/100 000 would have 1st and 2nd line treatments within 6 months from diagnosis. IRs for London and East Midlands were the highest (6.5/100 000). Conclusions: This study found a rising incidence of primary ITP, with sharp increases among young women and elderly men. These findings put in context the impact of ITP on patients' lives and the healthcare services in England, especially with 17%–50% who may develop chronic ITP and require long‐term care.